Static and Dynamic Brazilian Tests on Layered Slate considering the Bedding Directivity. (16th December 2020) - Ou, Xuefeng; Zhang, Xuemin; Feng, Han; Zhang, Cong; Zhou, Xianshun; Wang, Lei
Abstract : A layered rock usually exhibits strong anisotropy due to its layered structure. In order to study the anisotropic effect on its static and dynamic tensile properties, a medium strength anisotropy slate is chosen and tested in five groups of bedding plane dip angles. The dynamic tests were carried out by a split Hopkinson pressure bar (SHPB), and the failure process of rock samples is recorded by a high-speed camera. The failure mode and strength characteristic of the slate are analyzed. The static test results show that layered structure significantly affects the failure mode, and the influence of the bedding plane depends on the degree of anisotropy. The static and dynamic "tensile strength" exhibit the "U" type strength anisotropy. For samples in the same dip angle group, the "tensile strength" shows clear dynamic strengthening effect, and the growth rate is most significant at θ  = 45°.